Din eğitiminde Mücadele Suresi - Yavaş, Sümeyye Sultan Çevik (My University, 2008)
Bu çalışmanın amacı din eğitiminin önemli konularına Mücadele Suresi çerçevesinde bakmaktır. Tezin araştırma aşamasında surenin akışı göz önünde bulundurularak, “mücadele”, “kadın”, “adap”, “iletişim”, “dostluk”, “zikir” gibi konular incelenmiştir. Tez üç bölüme ayrılmıştır. cadele ve Kadın hakları” başlığında olup bu bölümde cedel, tartışma, mücadele, münazara gibi kavramlar incelenmiştir. Kur’an’ın kadına verdiği değer çeşitli başlıklar altında anlatılmaya çalışılmıştır. İkinci bölüm “Adab-ı Muaşeret” başlığında olup bu bölümde adap, muaşeret ve iletişim gibi kavramlar üzerinde durulmuştur. Ayrıca surede geçen adab-ı muaşeret kuralları incelenmiştir. Üçüncü bölüm “Allah Dostluğu ve Allah’ı Anma” başlığında olup bu bölümde de dostluk kavramı üzerinde durulmuştur. Dostluğun mahiyeti ve inananların kimleri dost edinip edinemeyeceği incelenmiştir. Ayrıca zikrin kelime anlamı, çeşitleri, mahiyeti incelenen konulardandır. Allah’ı zikretmenin faydaları ve zikre engel olan hususlar da incelenmiştir.

The purpose of this thesis is to look at important subjects of Education of Religion from the perspective of the Sura Mujadala-Struggle. During the research of the thesis, considering the context of the sura, the subjects as disputation, women, convenances, communication, friendship, remembering Allah were studied. The thesis includes three parts: The fist part is dedicated to Mujadilah/ Disputation and Women Rights. In this part, the following subjects are studied: dialectic, discussion, disputation, debate. The value that Qur’an gives women is studied to be explained under several headlines. The second part is dedicated to Good Form and Convenances. In this part, the following subjects are studied: good form, convenances and communication. Moreover, the rules of good form and convenances in the sura are also studied. The third part is dedicated to Friendship with Allah and Remembering Allah. In this part, the concept of friendship is studied. The characters of friendship and the concept of “whom to be friends for muslims and whom not” are analysed. Moreover, the meaning of the word “remembering Allah”, types and compositions of remembering are studied as well. The benefits of remembering Allah and the things that embarrasses remembering Allah are some other subjects that are studied.
Keywords: Din; Din Eğitimi; İslam Dini; Sureler_Din Eğitimi